Living With Obesity: Expressions of Longing - Venke Ueland PhD, RN; Elin Dysvik PhD, RN; Bodil Furnes PhD, RN (SAGE Publishing, 2020)
Abstract Those who are obese experience complex moral distress. The norm in Western societies is to be slim, and people living with obesity experience challenges under the gaze of society. They feel great vulnerability and the available treatments seldom meet individual needs. New concepts of embodiment need to be developed to include phenomenological investigations. There is limited knowledge about longing among those suffering from obesity. A deeper understanding of longing from an individual perspective is required to improve treatment. The aim of this study was to gain an in-depth understanding of the experiences of longing by those suffering from obesity. The research was approved by the Norwegian Regional Committees for Medical and Health Research Ethics. An explorative phenomenological-hermeneutical design was used. Qualitative interviews were conducted with 18 participants, all with body mass indexes in the range of 30 to 45, which were then analyzed using a phenomenological-hermeneutical approach. Three main dimensions of longing were revealed: longing for normality, longing for what was lost, and longing for simplicity in life. The health service needs to understand better the longings of obese individuals to help them live their lives in greater freedom, based on their own longings and self-care. Focusing on longing may reveal a person's true desires, and the longing may be a form of resistance to the disciplination of society.